Effect on the Dewatering of Oily Scum Caused by Ultrasound - Lu, Jiaang; Xu, Ning; Zhu, Yongjun; Jiang, Weili; Han, Pingfang; Lu, Xiaoping (Asian Journal of Chemistry, 2012)
About 15000 tons of oily scum with poor usage for their high water-containing can be produced per year by Yangtze Petrochemical Co. Refinery. Experiment using ultrasound for pre-processing to reduce the water-containing, as well as reducing the volume of the oily scum was presented. Results from single factor experiments and orthogonal experiments gave the optimum values of some factors influencing dehydration efficiency such as frequency, voltage, ultrasonic treatment time and temperature, sedimentation temperature, etc. The importance of each factor was determined. Compared with the original technology, the ultrasound method is obviously superior in saving the depletion of flocculants to make the processing cost much lower for the same result and meantime in making the water-containing of the oily scum lower in the same condition of sedimentation. The dewatered oily scum could be used in the delayed coking process.